The Effect of the Stretch-Shortening Cycle in the Force–Velocity Relationship and Its Association With Physical Function in Older Adults With COPD - Navarro-Cruz, Roberto; Alcazar, Julian; Rodriguez-Lopez, Carlos; Losa-Reyna, Jose; Alfaro-Acha, Ana; Ara, Ignacio; García-García, Francisco J.; Alegre, Luis M. (Frontiers in Physiology, 2019)
This study aimed to evaluate the effect of the stretch-shortening cycle (SSC) on different portions of the force–velocity (F–V) relationship in older adults with and without chronic obstructive pulmonary disease (COPD), and to assess its association with physical function. The participants were 26 older adults with COPD (79 ± 7 years old; FEV1 = 53 ± 36% of predicted) and 10 physically active non-COPD (77 ± 4 years old) older adults. The F–V relationship was evaluated in the leg press exercise during a purely concentric muscle action and compared with that following an eccentric muscle action at 10% intervals of maximal unloaded shortening velocity (V0). Vastus lateralis (VL) muscle thickness, pennation angle (PA), and fascicle length (FL) were assessed by ultrasound. Habitual gait speed was measured over a 4-m distance. COPD subjects exhibited lower physical function and concentric maximal muscle power (Pmax) values compared with the non-COPD group (both p < 0.05). The SSC increased force and power values among COPD participants at 0–100 and 1–100% of V0, respectively, while the same was observed among non-COPD participants only at 40–90 and 30–90% of V0, respectively (all p < 0.05). The SSC induced greater improvements in force, but not power, among COPD compared with non-COPD subjects between 50 and 70% of V0 (all p < 0.05). Thus, between-group differences in muscle power were not statistically significant after the inclusion of the SSC (p > 0.05). The SSC-induced potentiation at 50–100% of V0 was negatively associated with physical function (r = -0.40–0.50), while that observed at 80–100% of V0 was negatively associated with VL muscle thickness and PA (r = -0.43–0.52) (all p < 0.05). In conclusion, older adults with COPD showed a higher SSC-induced potentiation compared with non-COPD subjects, which eliminated between-group differences in muscle power when performing SSC muscle actions. The SSC-induced potentiation was associated with lower physical function, VL muscle thickness, and VL PA values. The SSC-induced potentiation may help as a compensatory mechanism in those older subjects with a decreased ability to produce force/power during purely concentric muscle actions.